Long-Term Increased Carnitine Palmitoyltransferase 1A Expression in Ventromedial Hypotalamus Causes Hyperphagia and Alters the Hypothalamic Lipidomic Profile - Mera, Paula (Public Library of Science, 2014)
Lipid metabolism in the ventromedial hypothalamus (VMH) has emerged as a crucial pathway in the regulation of feeding and energy homeostasis. Carnitine palmitoyltransferase (CPT) 1A is the rate-limiting enzyme in mitochondrial fatty acid β-oxidation and it has been proposed as a crucial mediator of fasting and ghrelin orexigenic signalling. However, the relationship between changes in CPT1A activity and the intracellular downstream effectors in the VMH that contribute to appetite modulation is not fully understood. To this end, we examined the effect of long-term expression of a permanently activated CPT1A isoform by using an adeno-associated viral vector injected into the VMH of rats. Peripherally, this procedure provoked hyperghrelinemia and hyperphagia, which led to overweight, hyperglycemia and insulin resistance. In the mediobasal hypothalamus (MBH), long-term CPT1AM expression in the VMH did not modify acyl-CoA or malonyl-CoA levels. However, it altered the MBH lipidomic profile since ceramides and sphingolipids increased and phospholipids decreased. Furthermore, we detected increased vesicular γ-aminobutyric acid transporter (VGAT) and reduced vesicular glutamate transporter 2 (VGLUT2) expressions, both transporters involved in this orexigenic signal. Taken together, these observations indicate that CPT1A contributes to the regulation of feeding by modulating the expression of neurotransmitter transporters and lipid components that influence the orexigenic pathways in VMH.